Optimizing the Function of Museums as a Medium for Evaluating History Learning in Supporting Students' Critical Thinking Skills - Rahmawati Rahmawati; Joko Sayono; Indah Wahyu Puji Utami; Ramli Akhmad (Universitas Hamzanwadi, 2025)
The use of museums as a medium for evaluating history learning plays a strategic role in improving the quality of the learning process while sharpening students' critical thinking skills. This study aims to evaluate history learning at the Learning Museum of Universitas Negeri Malang (UM), focusing on optimizing the museum’s role in supporting students' critical thinking abilities. A qualitative approach with a participatory design was employed, involving museum administrators, lecturers, and history students as key participants. Primary data were collected through participant observation and in-depth interviews, while secondary data were obtained from literature studies, documentation, and museum archives. Data analysis was conducted thematically through the stages of data reduction, display, and verification to ensure the validity of the findings. The results indicate that the application of a participatory approach in history learning at the museum significantly enhances student engagement, strengthens critical and reflective thinking skills, and fosters a deeper understanding of historical material. Students not only function as recipients of information but also actively engage in discussing historical contexts and reflecting on the relevance of historical values in contemporary life. Furthermore, the museum has proven to be an effective medium for authentic, contextual, and enjoyable learning evaluation, capable of bridging the gap between theory and practice. This study contributes to the literature on museums as a medium for participatory learning and critical thinking in history education. The findings also provide practical recommendations for museum administrators and educators in designing innovative history learning programs. More broadly, this research may serve as a reference for developing museum-based history learning strategies in Indonesia and at the international level.